2023
DOI: 10.1038/s41524-023-01005-8
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolatile electrical control of spin polarization in the 2D bipolar magnetic semiconductor VSeF

Abstract: Nonvolatile electrical control of spin polarization in two-dimensional (2D) magnetic semiconductors is greatly appealing toward future low-dissipation spintronic nanodevices. Here, we report a 2D material VSeF, which is an intrinsic bipolar magnetic semiconductor (BMS) featured with opposite spin-polarized valence and conduction band edges. We then propose a general nonvolatile strategy to manipulate both spin-polarized orientations in BMS materials by introducing a ferroelectric gate with proper band alignmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…In Figs. S3(d)-S3(i) in the ESM, m-RETaO 4 and t-RETaO 4 are less stable compared to the m' phase, which agrees with experimental findings [72] and other computational results [70]. Table 2 summarizes the equilibrium properties derived from the fitting of the four Birch-Murnaghan EOS, including volume (V 0 ), energy (E 0 ), bulk modulus (B 0 ), and its first derivatives relative to pressure (B').…”
Section: Crystal Structuresupporting
confidence: 90%
“…In Figs. S3(d)-S3(i) in the ESM, m-RETaO 4 and t-RETaO 4 are less stable compared to the m' phase, which agrees with experimental findings [72] and other computational results [70]. Table 2 summarizes the equilibrium properties derived from the fitting of the four Birch-Murnaghan EOS, including volume (V 0 ), energy (E 0 ), bulk modulus (B 0 ), and its first derivatives relative to pressure (B').…”
Section: Crystal Structuresupporting
confidence: 90%
“…reported that 2 H-VS 2 [21], NbS 2 [22], Tri-phase ReS 2 [23], 1 T ′ -CrS 2 [25], VSeF [26], GdI 2 [27], EuGe 2 [31], α-Fe 2 O monolayer [28] and the ternary 2D layered transition metal sulfides CrPX 4 (X = S, Se) [29], Cr 2 Ge 2 Te 6 [24]and Iron(III) halides FeM 3 (M = F, Cl) [30], GdXY (X,Y = S, Se) [32] etc., are all BMSs.…”
Section: Two-dimensional Intrinsic Bmsmentioning
confidence: 99%
“…The strong interlayer magnetoelectric coupling has been successfully established in layered HS multiferroics stacking up atomic layers of ferromagnets and FE materials, which realizes the control of magnetocrystalline anisotropy, magnetic phase transition, Dzyaloshinskii–Moriya interaction, , topological phase, and valley splitting . Particularly, the reversible switching from semiconductor to half-metal in 2D vdW HS based on the FE substrate not only realizes the generation of the spin-polarized carriers but also allows the manipulation, , which opens up the possibility for applications of 2D spintronics devices for memory storage, especially for 2D spin field-effect transistors (sFET). To achieve such device functions, FE materials are expected to always maintain semiconductor properties when they are in contact with ferromagnets.…”
Section: Introductionmentioning
confidence: 99%